Romanticism and the materiality of nature - Oerlemans, Onno, 1961- (University of Toronto Press, 2004)
Given current environmental concerns, it is not surprising to find literary critics and theorists surveying the Romantic poets with ecological hindsight. In this timely study, Onno Oerlemans extends these current eco-critical views by synthesizing a range of viewpoints from the Romantic period. He explores not only the ideas of poets and artists, but also those of philosophers, scientists, and explorers. Oerlemans grounds his discussion in the works of specific Romantic authors, especially Wordsworth and Shelley, but also draws liberally on such fields as literary criticism, the philosophy of science, travel literature, environmentalist policy, art history, biology, geology, and genetics, creating a fertile mix of historical analysis, cultural commentary, and close reading. Through this, we discover that the Romantics understood how they perceived the physical world, and how they distorted and abused it. Oerlemans's wide-ranging study adds much to our understanding of Romantic-period thinkers and their relationship to the natural world.